Peningkatan Pengetahuan Orangtua tentang Perkembangan Kognitif dan Sosial Peserta Didik di Kelurahan Sepinggan Balikpapan - Rahayu Sri Waskitoningtyas; Husnul Khotimah; Tri Hariyati Nur Indah Sari; Swasti Maharani (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2022)
The purpose of the socialization of student development is to find out about the cognitive development of students and the development of students socially. The socialization was held at Melati Anugerah Indah Housing RT 49, Sepinggan Village, Balikpapan City, East Kalimantan Province. The target/target of the socialization is the residents of Melati Anugerah Indah Housing with the criteria of parents who have elementary school children. The socialization was carried out by conducting interviews, questions and answers and documentation. Technically, the team held a socialization activity in one of the residents' houses. Participants in the socialization included parents with 20 elementary school-aged children. Based on the results of interviews and questions and answers, the results showed that (1) the cognitive development of students is a process of developing knowledge experienced by students related to the ability to think logically in solving a problem faced by students. The knowledge experienced by students can be continuously honed with a continuous process of training and learning both at school and outside of school, with the hope that when students face a new problem, students are able to solve it. (2) the social development of students is the process of developing student interactions with other friends in order to establish kinship and kinship relationships so that students can get along with each other.